Clinicians’ role in the prevention and management of neonatal candidiasis in Punjab: challenges and opportunities. - Stephen Monday; Atul Khajuria; Eric Kwasi Elliason; Gagan; J. Samuel Kamanda (Recent Trends in Infectious Diseases, 2025)
Background: Neonatal candidiasis is a growing concern in Punjab, particularly among newborns in neonatal intensive care units. The increasing prevalence poses significant risks to neonatal health, highlighting the need for effective management and prevention strategies. Objective: This study aims to explore the role of clinicians in preventing and managing neonatal candidiasis in Punjab while identifying the key challenges they face in clinical practice. Methods: A structured questionnaire was distributed to 350 clinicians, including pediatricians, neonatologists, and general practitioners, across both government and private healthcare facilities. The questionnaire gathered data on clinicians' awareness, practices, and challenges related to neonatal candidiasis. Results: Awareness: 78% of clinicians recognize neonatal candidiasis as a significant health issue. However, only 62% report having access to standardized treatment guidelines.Prevention Practices: 85% adhere to strict hygiene protocols, but only 54% consider routine screening for fungal infections to be a standard practice.Antifungal Prophylaxis: 72% believe antifungal prophylaxis should be given to high-risk neonates, but resource limitations and medication shortages hinder its implementation.Challenges: Key challenges identified include a lack of parental awareness (68%), limited access to diagnostic tools (59%), and antifungal medication shortages (53%). Additionally, 65% of clinicians expressed the need for greater government and institutional support to improve neonatal candidiasis management. Conclusion: The study underscores the urgent need for enhanced clinical guidelines, better resource allocation, and increased awareness initiatives to effectively manage neonatal candidiasis in Punjab. Addressing these challenges will empower clinicians to provide improved care and improve neonatal health outcomes.
Keywords: Antifungal Treatment; Clinicians' Role; Diagnostic Barriers; Healthcare Resources; Management Challenges; Neonatal Candidiasis; Neonatal Care; Punjab Healthcare; infection control; prevention strategies